Entrepreneurial website project “www.BusinessLetter4You.com” / Akmal Syaifudin Kaharudin ... [et al.] - Kaharudin, Akmal Syaifudin; Gafar@Abd Ghaffar, Siti Zuraina; Misman, Juritah (2021)
Graduates often lack the capability and soft skills critical to the modern business environment. According to Ruzaimi Mat Rani (2019), about 75 percent of project management is ineffective due to ineffective communication skills. Essentially, one of the most common incapabilities of our graduates to perform effectively in the real business environment is poor writing skills. Examples of poor writing skills include spelling errors, incorrect grammar and confusing messaging (Thompson, 2019). Poorly written business letters produce various negative results such as low productivity, poor customer satisfaction and loss of revenue. Moreover, there is insufficient material and information related to business letters on the Internet usable for the Malaysian contexts. In addition, it is observed that none of the current websites highlight sample material documents which could be referred to as guidelines specifically for business communication documents in Malaysia, resulting in a language barrier problem for the Bumiputras in expanding their businesses. Hence, our proposed website project called the “www.BusinessLetter4You.com: solving your business letters hassles” is created to solve all of the issues mentioned above. www.BusinessLetter4You.com is a website project aimed to be a platform which offers assorted guides and examples on different types of business letters while providing proofreading and translation services inclusively for business letters in Malaysia. This website project is to provide assistance for students or graduates to utilize in improving their writing skills and better prepare themselves for the workplace.